Age-related differences in the translational landscape of mammalian oocytes - Del Llano, Edgar; Masek, Tomas; Gahurova, Lenka; Pospisek, Martin; Koncicka, Marketa; Jindrova, Anna; Jansova, Denisa; Iyyappan, Rajan; Roucova, Kristina; Bruce, Alexander W; Kubelka, Michal; Susor, Andrej (Aging cell, 2020)
Increasing maternal age in mammals is associated with poorer oocyte quality, involving higher aneuploidy rates and decreased developmental competence. Prior to resumption of meiosis, fully developed mammalian oocytes become transcriptionally silent until the onset of zygotic genome activation. Therefore, meiotic progression and early embryogenesis are driven largely by translational utilization of previously synthesized mRNAs. We report that genome-wide translatome profiling reveals considerable numbers of transcripts that are differentially translated in oocytes obtained from aged compared to young females. Additionally, we show that a number of aberrantly translated mRNAs in oocytes from aged females are associated with cell cycle. Indeed, we demonstrate that four specific maternal age-related transcripts (Sgk1, Castor1, Aire and Eg5) with differential translation rates encode factors that are associated with the newly forming meiotic spindle. Moreover, we report substantial defects in chromosome alignment and cytokinesis in the oocytes of young females, in which candidate CASTOR1 and SGK1 protein levels or activity are experimentally altered. Our findings indicate that improper translation of specific proteins at the onset of meiosis contributes to increased chromosome segregation problems associated with female ageing.
Keywords: savci; oocyty; Female; Age Factors; věkové faktory; Animals; ženské pohlaví; Humans; Oocytes; lidé; zvířata; Mammals